Functional Piezoresistive Polymer‐Composites Based on Polycarbonate and Polylactic Acid for Deformation Sensing Applications. Issue 12 (18th September 2020) - Dios, Jose R.; Gonzalo, Beatriz; Tubio, Carmen R.; Cardoso, João; Gonçalves, Sérgio; Miranda, Daniel; Correia, Vitor; Viana, Júlio C.; Costa, Pedro; Lanceros‐Méndez, Senentxu
Abstract: Multifunctional composites for deformation sensing applications have been developed by solvent casting based on polycarbonate (PC) and polylactic acid (PLA) reinforced with carbon nanotubes (CNT). Composites shows homogeneous filler dispersion and low percolation threshold at 0.1 and 0.06 wt% CNT content for PLA and PC, respectively. The maximum electrical conductivity obtained for the larger filler contents is two order of magnitude higher for PLA composites than for PC ones, showing that the matrix influences the electrical properties of the composites. With respect to the mechanical characteristics, the samples show a maximum strain near 40% and 2.75% for composites with 0.25 and 1 wt% CNT content for PC and PLA, respectively, decreasing for larger filler contents. Concerning the piezoresistive response, 4‐point‐bending experiments from 0.1 to 5 mm, lead to a Gauge Factor (GF) of ≈1 for PC, showing that the piezoresistive response if determined by the geometrical response. On the other hand, PLA composites show GF of ≈ 3, revealing also intrinsic contributions, due to the variation of the filler network upon material deformation. The resistance variation upon mechanical bending deformation shows linear response for the composites near the percolation threshold and above, for both composites. A proof‐of‐concept of the functional sensing response for applications is achieved by measuring the bending deformation of an endoscope, showing that the developed sensors can determine the bending orientation and intensity, as predicted by the simulation model applied to the endoscope. Abstract : Polylactic acid (PLA) and polycarbonate (PC) composites with carbon nanotubes are developed as multifunctional materials by tailoring their electrical conductivity. The composites above the electrical percolation threshold work are evaluated as functional deformation sensors. Further, the suitability of the developed materials for applications is demonstrated by their implementation in an endoscope, allowing to determine its deformation in real time.